Coherent or conflicting? Assessing natural gas subsidy and energy efficiency policy interactions amid CO2 emissions reduction in Malaysia electricity sector - Babatunde K.A.; Said F.F.; Md Nor N.G.; Begum R.A.; Mahmoud M.A. (Elsevier Ltd, 2023)
Carbon dioxide; Electric industry; Electric utilities; Emission control; Energy policy; Energy utilization; Environmental technology; Gas emissions; Greenhouse gases; Growth rate; Natural gas; Natural gasoline plants; Agent-based computational economics; Average annual growth rates; Carbon dioxide emissions; Emission reduction potentials; Emission reduction targets; Energy efficiency policies; Environmental consequences; Low-carbon technologies; Energy efficiency